The Validity and Reliability of Turkish Version of Job Satisfaction Scale for Nurses - Aysun Türe Yılmaz; Aytolan Yıldırım (Association of Nurse Managers, 2017)
INTRODUCTION: The job satisfaction of nurses is related with turnover rate, productivity in service, quality and patient satisfaction. This study has been planned with the purpose of firstly testing the validity and reliability of 'Job Satisfaction Scale for Nurses' and then bring it in to the nursing literature. METHODS: This is a methodological study. The sample of the study is composed of 964 nurses working in both a university hospital (N=550) and a state hospital in Eskisehir city centre. The data have been collected through 'Job Satisfaction Scale for Nurses' developed by Muya et al. (2014) and 'Personal Information Form'. The scale has been tested in terms of language validity, scope validity, and internal consistency at the validity and reliability stage through test-retest method. RESULTS: According to statistical analyses, it has been found out that JSSN's test-retest reliability coefficient is α=0,96, correlation value r=0,973 and p=0,000. There is no significant difference between the average scores of test-retest. The reliability of internal consistency has been found as α= 0,90. It has been specified that the correlation values of total score of items are between 0,32 and 0,69; after the confirmatory factor analysis, the factor load of items are between 0,40 and 0,96, and 4-factor structure of the scale is acceptable.It has been determined that the 'Job Satisfaction Scale for Nurses' has been composed of 27 items and 4 sub-dimensions which are 'Positive Feelings towards the Job', 'Suitable Support from Seniors', 'Perceived Importance at the Job', and 'Pleasant Work Environment'. DISCUSSION AND CONCLUSION: At the end of the analyses, it has been found out that the 'Job Satisfaction Scale for Nurses' is a valid and reliable scale to be applied to Turkish society.